'Anything but heavy meal' – Culinary dislikes and patterned intolerance among the young urban Finns. (March 2019) - Lindblom, Taru; Mustonen, Pekka
Perceiving various lifestyles as unpleasant is considered as an indicator of symbolic boundaries distinguishing between social groups. This article examines culinary dislikes covering various cuisine types. Using Finnish data collected among young urban adults (n = 1706), we find that disliking various cuisine types (19 in total) is particularly patterned and somewhat determined by socio-demographic factors. Dislikes are clustered according to legitimacy and exoticness in four components: 'Culinary canon', 'Fast and Convenient', 'Ethnic' and 'Familiar'. Furthermore, a large group of categorical tolerant people is observed. As expected, socially more 'well-to-do' groups show less dislike towards various cuisines types. However, higher statuses are selective and very specific in terms of certain dislikes thus showing signs of patterned intolerance (à la Bryson). The highly educated dislike particularly less cuisine types belonging to 'Culinary canon', whereas 'Fast and Convenient' are clearly less tolerated. Categorical tolerance towards food is more a sign of cultural goodwill than new form of omnivorousness.